Zambia : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report, 2008)
The fiscal stance has been more expansionary in 2008, but there should be no need for net domestic financing. The new fiscal regime for mining increases the average effective tax rate from a level that was significantly below that of other mining countries. The monetary program aims to reduce annual inflation to 7 percent in 2008. The authorities intend to address the challenge of coordinating fiscal and monetary policies to enable the Bank of Zambia (BoZ) to improve liquidity management. Structural policies will complement the medium-term macroeconomic framework.